If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2=x-2-3x+6
We simplify the equation to the form, which is simple to understand
2=x-2-3x+6
We move all terms containing x to the left and all other terms to the right.
-1x+3x=-2+6-2
We simplify left and right side of the equation.
+2x=+2
We divide both sides of the equation by 2 to get x.
x=1
| -5x-5x=35-5 | | Bx-d=ax+c | | 15f^2+37f-8=0 | | m+4m+9m+2= | | 880/74 | | -23+10=m-5 | | 14/63 | | 435/15 | | 5y-10=25x | | C=1000+0.6(Y-200) | | 4x+9=57-4x | | 6x=6(70-x) | | 7t+44=12y+11 | | m+3m-9m= | | 2x^2-15x=9 | | -5x=-28+2x | | 28x-28x-56=56 | | -2/5y=1 | | a(x+1)(x+4)= | | 80000=-x^2+1400x-1320000 | | Z=880+0.6Y+500+250 | | -3x+29=8 | | 5-4x=-3x+15 | | -5x+16=-4x+13 | | 8x+7-7x=9x-2+x | | x+(2/3)x=55 | | 2(4x+4)+6=3x+9 | | 6x=6(70+x) | | -3x+16=-6x+22 | | -6x+7=7x-32 | | 2x-10=4(3x-1)+4 | | 7x+22=-x+86 |